KESANTUNAN BERBAHASA DALAM NOVEL SURGA UNTUK IBUKU KARYA RIRI ANSAR: KAJIAN PRAGMATIK - Roby Afandi; Patriantoro Patriantoro; Amriani Amir (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis research uses descriptive method in a qualitative form using documentary study techniques. The data source in this research is the novel Surga Untuk Ibuku by Riri Ansar in the form of a speech or dialogue betweencharacters. The data collection tool is the researcher as a key instrument assisted by notes in the form of inter-character speeches which contain the principle of politeness according to Leech in the novel Surga Untuk Ibuku by Riri Ansar. The technique of testing the validity of the data was carried out using three techniques, namely observer persistence, reference adequacy, and peer examination. The research results in this study were 59 utterances. The maxim of generosity consists of 14 utterances, the maxim of sympathy is 7 utterances, the maxim of appreciation is 5, the maxim of wisdom is 10, the maxim of simplicity is 3, the maxims of consensus are 2, very polite utterances are 4, the polite utterances are 4, utterances very impolite amounted to 5 utterances, and disrespectful speech totaled 5 utterances. Based on the results of the research analysis, it can be concluded that the maxim of generosity, maxim of wisdom, utterance is very impolite, and very few utterances in the novel Surga Untuk Ibuku by Riri Ansar are the maxims of consensus and simplicity.Keywords: pragmatic, the principle of politeness, novel